STRUCTURAL AND FUNCTIONAL CONDITION OF THE KNEE JOINT IN PATIENTS WITH MONOGONARTHROSIS IN THE STAGE OF EXACERBATION - Taras Khanyk (Acta Medica Leopoliensia, 2022)
The goal is to study the structural changes of the elements of the knee joint and their functional consequences in patients with monogonarthrosis of the 1st-2nd grade in the stage of exacerbation according to the data of a complex clinical and arthroscopic study.